2016
DOI: 10.1016/j.bbagen.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol compounds and PKC signaling

Abstract: Background Naturally occurring polyphenols found in food sources provide huge health benefits. Several polyphenolic compounds are implicated in the prevention of disease states, such as cancer. One of the mechanisms by which polyphenols exert their biological actions is by interfering in the protein kinase C (PKC) signaling pathways. PKC belongs to a superfamily of serine-threonine kinase and are primarily involved in phosphorylation of target proteins controlling activation and inhibition of many cellular pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 269 publications
(273 reference statements)
2
57
0
3
Order By: Relevance
“…25 Phosphorylation of Nrf2 allows the Nrf2 to translocate to the nucleus and bind to the antioxidant response element in the regulatory region of the target genes and induces the transcription of antioxidant enzymes. 26 Pre-clinical studies have shown that orally delivered curcumin has neuroprotective effects 27 and has been found to reduce lipid peroxidation by maintaining the activities of antioxidant enzymes such as CAT, SOD, GPx, and GSH levels in rats exposed with neurotoxic compounds. 28,29 The ability of curcumin to increase the GSH levels is due to its affinity to induce the transcription of the mRNAs for the GSH biosynthetic genes.…”
Section: Discussionmentioning
confidence: 99%
“…25 Phosphorylation of Nrf2 allows the Nrf2 to translocate to the nucleus and bind to the antioxidant response element in the regulatory region of the target genes and induces the transcription of antioxidant enzymes. 26 Pre-clinical studies have shown that orally delivered curcumin has neuroprotective effects 27 and has been found to reduce lipid peroxidation by maintaining the activities of antioxidant enzymes such as CAT, SOD, GPx, and GSH levels in rats exposed with neurotoxic compounds. 28,29 The ability of curcumin to increase the GSH levels is due to its affinity to induce the transcription of the mRNAs for the GSH biosynthetic genes.…”
Section: Discussionmentioning
confidence: 99%
“…ROS reduction) remain to be clarified but our preliminary in silico analysis suggests that it is unlikely through a direct binding of curcumin to the AHR-1 ligand binding domain. Accordingly, while direct ligandbinding has not been verified for many of the polyphenolic AhR modulators, ligandindependent effects on AhR signaling, like binding to HSP90 (Palermo, Westlake et al, 2005) or inhibition of AhR phosphorylation by the protein kinase C (Das, Ramani et al, 2016, Nishiumi et al, 2007 , have been instead described.…”
Section: Discussionmentioning
confidence: 99%
“…To further determine the relative affinity of curcumin for the αC1A and αC1B sub-domains, we studied their interactions with curcumin using a fluorescence assay previously used to study the effect of resveratrol with PKC (55). Resveratrol is another naturally occurring polyphenol known for its interaction with PKC (56). Our results show that phorbol 13-acetate displaced curcumin from αC1A and αC1B with IC 50 values of 6.27± 1.2 μM and 4.47±1.7 μM, respectively, indicating slightly higher affinity of the αC1B than αC1A.…”
Section: Discussionmentioning
confidence: 99%